2020
DOI: 10.1177/1532673x20923588
|View full text |Cite
|
Sign up to set email alerts
|

Do More Professionalized Legislatures Discriminate Less? The Role of Staffers in Constituency Service

Abstract: Research suggests that organizational structure can influence the ability of actors to discriminate. In this research note, we examine whether the structure of state legislatures affects observed discrimination in correspondent audit studies. We find that increased legislative professionalization is associated with reduced discrimination against racial minorities. By analyzing thousands of emails collected in a prior study, we find that legislative professionalization is related to a higher likelihood that sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…We offer evidence to support our hypothesis that state legislators believe there is an indirect reward for helping undocumented immigrants, but prioritize them below that of citizens, who offer a more direct reward. It is important to note that responsiveness is tied to the professionalization of the legislature, giving support to our supposition that greater resources make responsiveness less costly for legislative offices (Landgrave and Weller 2020). Our paper leaves us with some more important questions, including whether the Latinx community, regardless of citizenship status, are racialized as foreign-born without the help of a citizenship signifier.…”
Section: Discussionmentioning
confidence: 87%
“…We offer evidence to support our hypothesis that state legislators believe there is an indirect reward for helping undocumented immigrants, but prioritize them below that of citizens, who offer a more direct reward. It is important to note that responsiveness is tied to the professionalization of the legislature, giving support to our supposition that greater resources make responsiveness less costly for legislative offices (Landgrave and Weller 2020). Our paper leaves us with some more important questions, including whether the Latinx community, regardless of citizenship status, are racialized as foreign-born without the help of a citizenship signifier.…”
Section: Discussionmentioning
confidence: 87%
“…Landgrave and Weller (2020) have suggested that discrimination is mediated by state-level professionalization. In a more professionalized legislature, legislators are less likely to handle constituent communications as their staff often handles constituent service.…”
Section: Resultsmentioning
confidence: 99%
“…Their location gives them regular and frequent access to voters, the local party and party supporters (Michon, 2014). Hence, they are well-placed to research constituents’ preferences and advise MPs on how to be policy responsive (Kaslovsky, 2022; Landgrave and Weller, 2020; Russell, 2004; Tomkova, 2014). Local staff participate in town hall meetings and stay in touch with local party leaders; they help hold surgeries and discuss matters of concern to constituents.…”
Section: Parliamentary Allowancesmentioning
confidence: 99%